Biosynthesis, Anti-TB Activity and Degradation of Dyes by Silver Nanoparticles using Fruits Peels - Kaur, Harpreet; Sharma, Abhinav (Asian Journal of Chemistry, 2019)
In the present work, waste materials such as pomegranate and orange peels were taken to synthesize nanoparticles by biological method. The method did not involve the use of toxic reducing and capping agents. It uses only the environmentally benign biomolecules for reduction of AgNO3 and subsequent stabilization of silver nanoparticles. The size of pomegranate and orange silver nanoparticles varied from 8-25 nm with nearly spherical morphology as analyzed by XRD and TEM studies. The synthesized nanoparticles were studied for their dye degrading property. Different dyes such as crystal violet, methylene blue, malachite green and Congo red were taken for the study. The results indicated the presence of two diverse mechanism of dye removal. Crystal violet, methylene blue, malachite green was removed by adsorption onto both the nanoparticles, whereas Congo red was reduced by NaBH4 in the presence of catalytic pomegranate silver nanoparticles. Moreover, pomegranate silver nanoparticles have exhibited potent antitubercular activity with MIC value of 6.25 μg/mL and orange silver nanoparticles are moderately active with MIC value of 25 μg/mL. It could be concluded that the pomegranate silver nanoparticles would a promising candidate for drug development and catalysis.